(Coconut oil Extraction Using The Intermidiate Moisture Content Technology) - Dadang Supriatna; Bakri Rosidi; Hitler Guring Pohan (Warta Industri Hasil Pertanian, 2000)
Alternative technology to extract the coconut oil has been improved and investigated. this technology was the intermediate moinsture content (IMC) technology which is suitble for small and medium scale industry. the main product is virgin coconut oil which is to be used for cooking without further chemical treatment and also used in cosmetic and pharmacy industry. the by-product that is low fat dried grated coconut flesh can be used in bakery industry. the observation done were moinsture content of dried grated coconut flesh before pressing, oil yield, oil noisture ontent, free fatty acid (FFA), organoleptic test, and shelf life. the moinsture and oil content of the by-product was also analysed, along with the mass balance, and techno-economic analysis. the result showed that the FFA and moinsture content of the oil met the requirements of the Indonesian National Standars pf cooking oil during 3 monts. storage. the organoleptic test showed that the virgin oil was more acceptable than refined coconut oil that sold in the market. the techno-economic analysis showed that using the capacity of 80 nuts/day, the profit would be Rp. 745,450,- per month, and the pay back period would be 3.24 year.